To Determine the Frequency of Biochemical Adverse Effects in Patients on Meglumine Antimoniate Treatment for Cutaneous Leishmaniasis (Medical Forum Monthly, 2024)
Objective: To determine frequency of biochemical adverse effects in patients on meglumineantimoniate treatment for cutaneous leishmaniasis.Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Dermatology, Bolan Medical College/ Sandeman Provincial Hospital, Quetta from January, 2017 to December, 2018.Materials and Methods: A total of 241patients with the diagnosis of CL were included in this study. The patients were treated with intra-gluteal injections of MA (Glucantime; Aventis, France) at a dose of 20mg/kg/day for 21 days. Patients were interviewed regarding their basic demographics. Blood samples were taken at 2nd week after starting treatment. Blood was sent for complete blood count, liver functions tests, serum creatinine and serum amylase level. Data was analyzed using SPSS version 23.Results: A total of 241 patients were included in the study. The mean age of the patients was found to be 26.04 ± 9.23 years. The gender distribution of patients showed that most of the participants were male in this study. Mean BMI was 29.25 ± 5.34 kg/m2. Most of the patients were having their symptoms from 4-8 weeks. Regarding the abnormality in biochemical variables after start of treatment, it was observed that the most commonly deranged variable was serum amylase in 66 patients (27.3%), followed by alkaline phosphatase in 56 patients (23.23%), ALT levels in 47 patients (19.5%) and serum AST levels in 41 patients (17.01%). Stratification of all these variables was done for age, gender, BMI levels and duration since start of symptoms and was significant for very few of them.Conclusion: It is concluded that biochemical changes in patients of cutaneous leishmaniasis taking meglumineantimoniate do occur. Therefore, we need to educate our patients and need to tell them about the expected changes before the start of treatment with meglumineantimoniate.